2021
DOI: 10.1016/j.jhep.2021.04.027
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the Freiburg index of post-TIPS survival

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…In the present study, however, while the FIPS score demonstrated a numerically higher discrimination versus MELD, MELD-Na, and CTP in the entire cohort, there was no appreciable improvement over MELD-Na in the modern TIPS era from 2014 to 2020. This was similarly seen in another small, single center study in which 104 patients receiving TIPS implantation between 2013 and 2018 demonstrated the FIPS score's poorer discriminatory performance when compared with MELD and CTP [21]. There are several potential explanations for this observation.…”
Section: Discussionmentioning
confidence: 60%
“…In the present study, however, while the FIPS score demonstrated a numerically higher discrimination versus MELD, MELD-Na, and CTP in the entire cohort, there was no appreciable improvement over MELD-Na in the modern TIPS era from 2014 to 2020. This was similarly seen in another small, single center study in which 104 patients receiving TIPS implantation between 2013 and 2018 demonstrated the FIPS score's poorer discriminatory performance when compared with MELD and CTP [21]. There are several potential explanations for this observation.…”
Section: Discussionmentioning
confidence: 60%
“…Due to the low number of high-risk patients the FIPS score did not show superior prognostic accuracy compared to the model for endstage liver disease (MELD) and Child-Pugh score. 1 Importantly, the authors mention that their cohort was similar to our FIPS cohort. 3 However, after reviewing the detailed description of the baseline characteristics of their study cohort, 4 it has to be mentioned that there are important differences compared to the FIPS cohort.…”
mentioning
confidence: 69%
“…To the Editor: With great interest, we have read the letters from Kraglund et al 1 and Wang et al 2 who provided external validation of the FIPS score 3 and also proposed a detailed risk stratification combining the Child-Pugh score and the FIPS score.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22 However, in two external validation cohorts, the superiority of FIPS over MELD and Child-Pugh scores could not be confirmed. 23,24 The present study aimed to develop a modified TIPS score (MOTS), based on MELD, the current gold standard of post-TIPS mortality prediction, that can be calculated from routine laboratory parameters without any technical help and is widely applicable.…”
Section: Introductionmentioning
confidence: 99%